PENGETAHUAN TENAGA KESEHATAN TENTANG PENCEGAHAN INFEKSI DI RSUD PURBALINGGA - Linda Yanti; Eni Wiyatun (Viva Medika, 2012)
Background: Infection Prevention is essential to power in 2011 in hospitals kesehatan.Pada Purbalingga, a number of clients experiencing 1.17% of nosocomial infections. In February2011 there were 0.2% of patients experienced plebitis and 1.21% for patients dikubitus. Thenin May 2011 amounted to 1.25% and 0.16% suffered decubitus plebitis patients. Objective: To determine the knowledge of health personnel on the prevention of infection.Methods: This research method is deskriptif.Data used primary data and is taken by using accidental sampling technique is a way of sampling the chance to meet and instrumenya arequestionnaires to 52 medical personnel in hospitals Purbalingga. Results: Knowledge of health personnel on the prevention of infection of 52 respondents, themajority of health workers is a good knowledge of as many as 28 respondents (53.8%) and asmall portion of knowledge of health workers is less by 10 respondents (19.3%). Conclusion: Overview Knowledge About Health Workers in Hospital Infection PreventionPurbalingga in 2012 showed that the knowledge of health personnel on the prevention ofinfection of 52 respondents, the majority of health workers is a good knowledge of as manyas 28 respondents (53.8%). Keywords: Knowledge, Prevention infection, Medicals